EVALUATION OF ORTHOPEDIC TREATMENT WITH REMOVABLE DENTAL PROSTHESES FOR PATIENTS WITH PAIR PATHOLOGY - Burxonova Zarafruz Qobilovna, Egamov Azizjon Nodirovich (Journals Park Publishing, 2023)
For a long time, orthopedic treatment of chronic generalized periodontitis with defects in the dentition in patients with diabetes mellitus has been a multifactorial and complex task [1, 2]. It is known that diabetic complications affect many organs and systems of the body, the oral cavity is a paramount indicator, characterized by vascular, neurological, metabolic, structural disorders of the hard tissues of the teeth, periodontal tissues, oral mucosa and other manifestations [5]. As a rule, these can be changes of an inflammatory and dysbiotic nature, accompanied by halitosis, impaired sensitivity of the mucous membrane, and taste perception. In addition, there are common forms of stomatitis (catarrhal, aphthous, ulcerative), candidal changes and lichen planus of the oral mucosa (OM), periodontitis with varying degrees of mobility, loss of alveolar bone and depth of the periodontal pocket.
Keywords: dentistry, removable orthopedic structures, atrophy, diabetes mellitus, oral dysbiosis, thermoplastic base polymers.